Pseudoaneurysm of the mitral-aortic intervalvular fibrosa. (January 2015) - Lin, Albert; Poppas, Athena; Mansoor, Atizaz; Fernandez, Antonio B.
Abstract : A pseudoaneurysm of the mitral-aortic intervalvular fibrosa is a rare but potentially fatal complication seen primarily in the context of infective endocarditis. In this study, we discuss a case of infective endocarditis that was complicated by the rupture of a pseudoaneurysm of the mitral-aortic intervalvular fibrosa. We review the salient echocardiographic findings of this clinical condition.